Influence of matrix nature on the functional efficacy of biomedical cell product for the regeneration of damaged liver (experimental model of acute liver failure) - S. V. Gautier (Vestnik Transplantologii i Iskusstvennyh Organov, 2017)
Aim. A comparative analysis of the functional efficacy of biomedical cell products (BMCP) for the regeneration of damaged liver based on biopolymer scaffolded porous and hydrogel matrices was performed on the experimental model of acute liver failure. Materials and methods. Matrices allowed for clinical use were employed for BMCP in the form of a sponge made from biopolymer nanostructured composite material (BNCM) based on a highly purified bacterial copolymers of poly (β-hydroxybutyrate-co-β-oxyvalerate) and polyethylene glycol and a hydrogel matrix from biopolymer microheterogeneous collagen-containing hydrogel (BMCH). Cellular component of BMCP was represented by liver cells and multipotent mesenchymal bone marrow stem cells. The functional efficacy of BMCP for the regeneration of damaged liver was evaluated on the experimental model of acute liver failure in Wistar rats (n = 40) via biochemical, morphological, and immunohistochemical methods. Results. When BMCP was implanted to regenerate the damaged liver on the basis of the scaffolded BNCM or hydrogel BMCH matrices, the lethality in rats with acute liver failure was absent; while in control it was 66.6%. Restoration of the activity of cytolytic enzyme levels and protein-synthetic liver function began on day 9 after modeling acute liver failure, in contrast to the control group, where recovery occurred only by days 18–21. Both matrices maintained the viability and functional activity of liver cells up to 90 days with the formation of blood vessels in BMCP. The obtained data confirm that scaffolded BNCM matrix and hydrogel BMCH matrix retain for a long time (up to 90 days) the vital activity of the adherent cells in the BMCP composition, which allows using them to correct acute liver failure. At the same time, hydrogel matrix due to the presence of bioactive components contributes to the creation of the best conditions for adhesion and cell activity which accelerate the regeneration processes in the damaged liver compared to BMCP on scaffolded matrix. Conclusion. A statistically significant difference was found between the functional efficacy of the BMCP studied based on BNCM and BMCH matrices. BMCP based on hydrogel BMCH matrix was more effective for the regeneration of damaged liver.